Identifikasi Pemahaman Konsep Siswa pada Materi Hidrolisis Garam di Kelas XI SMA Negeri 3 Gorontalo Menggunakan Test Diagnostik Three Tier Multiple Choice - Mardjan Paputungan; Mangara Sihaloho; Erga Kurniawati; Karmila B. Enu (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
This research aims to determine student’s conceptual understanding of salt hydrolysis in 11th grade at SMA Negeri 3 Gorontalo using a three-tier multiple-choice diagnostic test. This research employs qualitative descriptive research, with the subjects being 156 students from the 11th grade chemistry class at SMA Negeri 3 Gorontalo. Data was collected using a three-tier multiple-choice diagnostic test consisting of 20 question. The results indicate that, on average, students only understand 18,12% of the salt hydrolysis concept, 43,54% of students experience misconceptions and 38,34% do not understanding the concept. From the identifikation results, the highest level of conceptual understanding was found in indicator 1, which determines the acidic and basic properties of salt-forming compounds, with a percentage 21,66%. The highest level of miskonceptions was found in indicator 2, which analyzes the properties of hydrolyzed salts, with an average of 54,03% and the highest level of lack of understanding was found in indicator 4, which calculates the pH of a hydrolyzed salt solutions, with an average of 47,4%. Overall, it can be stated that 81,88% of students do not correcly understand the material on salt hydrolysis. The indicates that students’ conceptual understanding of salt hydrolysis is very low.